Molecular interaction study of L-Ornithine with bovine serum albumin using spectroscopic and molecular docking methods - Sakshi Koundal; Apoorva Pathania; Harman Deep Kour; Anu Radha Pathania; Jatinder Kaur; Bhanu Juneja; Girish Chandra Sharma; Abhijit Bhowmik; A. Johnson Santhosh (Scientific Reports)
Abstract Activates the pituitary gland, leading to increased secretion of growth hormone. This activation plays a crucial role in growth, metabolism, and tissue repair. Bovine serum albumin, a well-studied protein, demonstrates the interaction between proteins-ligands and transports various compounds in the bloodstream. This study elucidates the molecular interactions between L-ornithine and BSA through spectroscopic analysis, identifying binding modes, constants, and structural changes. Molecular docking techniques are employed to correlate with experimental data from fluorescence and UV spectroscopy analyses.The study uses Fourier transform infrared spectroscopy, UV–Visible spectroscopy, fluorescence spectroscopy, circular dichroism spectroscopy and molecular docking to analyze the interaction between bovine serum albumin and L-ornithine, providing thermodynamic parameters for understanding the protein structure and its binding.The interactions between L-ornithine and bovine serum albumin (BSA) were characterized using UV–visible spectroscopy, which demonstrated a hyperchromic shift. Fluorescence spectroscopy revealed that L-ornithine quenches the intrinsic fluorescence of both BSA and human serum albumin (HSA) via a static quenching mechanism, resulting in the formation of stable BSA-L-ornithine and HSA-L-ornithine complexes. Furthermore, Fourier-transform infrared (FTIR) and circular dichroism (CD) spectroscopy indicated a decrease in the secondary structure of the proteins, as evidenced by shifts in the amide II band and a concomitant reduction in α-helix content. Molecular docking studies suggested that L-ornithine binds to BSA within subdomain II. Collectively, these findings provide valuable insights into the metabolic pathways of L-ornithine and its potential pharmacological relevance. The study involves more precise information which revealing the insight of L-ornithine bioavailability. The finding enhances our understanding of interaction with potential implications for drug delivery.